Microscopic and ultramicroscopic changes of the gastric mucosa chief exocrinocytes under the influence of sublethal general dehydration of the organism - Hula, V. I.; Sikora, V. Z.; Yarmolenko, O. S.; Bumeister, V. I.; Pernakov, M. S.; Boiko, V. O. (Zaporozhye Medical Journal, 2018)
The functional state of the gastric mucosa chief cells reflects the ability to break down proteins and fully absorb the substances which are vital for the body under the influence of severe general dehydration of the organism. The aim To reveal morphological and ultramicroscopic changes of the gastric fundus chief exocrinocytes of rats under the influence of sublethal general dehydration of organism. Materials and methods. The influence of sublethal general dehydration was modeled on mature laboratory rats of the experimental series that was achieved on the 9th day of the experiment. During the experiment the animals were kept based on a complete waterless regime and fed dry granulated food. Samples for microscopic and ultramicroscopic studies were prepared according to generally accepted techniques. The results were evaluated using light microscope "Olympus" with a photographic registration of the morphological picture by a Baumer / optronic video camera. Type: CX05c and by electron microscope EM-125. Morphometric studies were carried out using the program «Digimizer». Results. The average values of the cross-sectional area of the chief cells cytoplasm and nuclei, their microscopic and ultramicroscopic changes under influence of severe general dehydration of the organism were studied. Conclusions. Severe general dehydration of the organism is accompanied by a decrease in the total number of the oxyntic cell in gastric glands by 21.22 % (P < 0.0001) and in the number of chief exocrinocytes per one gland by 19.43 % (P < 0.0001), relative to the control group. Percentage of the chief exocrinocytes in the gastric glands on the 9th day of the experiment is 37.66 %. A morphometric study has revealed a decrease in the cross-sectional area of the cells cytoplasm by 37.73 % (P < 0.0001), of nuclei by 21.97 % (P = 0.0110). Ultrastructural transformations of the chief exocrinocytes are signs of a sharp decrease in synthetic processes intensity in these cells, as well as a violation of not only the secret synthesis, but also the process of its secretion from the cytoplasm. The revealed ultrastructural changes in the cell organelles of the gastric fundic glands chief exocrinocytes are results of hypoxic alteration and metabolic disturbances (as general dehydration manifestations) and are destructive-dystrophic with the transformation into necrobiotic nature.